Pupal Diapause Termination and Transcriptional Response of Antheraea pernyi (Lepidoptera: Saturniidae) Triggered by 20-Hydroxyecdysone - Du, Jie; Zhao, Ping; Wang, Jiazhen; Ma, Sanyuan; Yao, Lunguang; Zhu, Xuwei; Yang, Xinfeng; Zhang, Xian; Sun, Zhenbo; Liang, Shimei; Xing, Dongxu; Duan, Jianping (Frontiers in Physiology, 2022)
The pupal diapause of univoltine Antheraea pernyi hampers sericultural and biotechnological applications, which require a high eclosion incidence after artificial diapause termination to ensure production of enough eggs. The effect of pupal diapause termination using 20-hydroxyecdysone (20E) on the eclosion incidence has not been well-documented in A. pernyi. Here, the dosage of injected 20E was optimized to efficiently terminate pupal diapause of A. pernyi, showing that inappropriate dosage of 20E can cause pupal lethality and a low eclosion incidence. The optimal ratio of 20E to 1-month-old pupae was determined as 6 μg/g. Morphological changes showed visible tissue dissociation at 3 days post-injection (dpi) and eye pigmentation at 5 dpi. Comprehensive transcriptome analysis identified 1355/1592, 494/203, 584/297, and 1238/1404 upregulated and downregulated genes at 1, 3, 6, and 9 dpi, respectively. The 117 genes enriched in the information processing pathways of “signal transduction” and “signaling molecules and interaction” were upregulated at 1 and 3 dpi, including the genes involved in FOXO signaling pathway. One chitinase, three trehalase, and five cathepsin genes related to energy metabolism and tissue dissociation showed high expression levels at the early stage, which were different from the upregulated expression of four other chitinase genes at the later stage. Simultaneously, the expression of several genes involved in molting hormone biosynthesis were also activated between 1 and 3 dpi. qRT-PCR further verified the expression patterns of two ecdysone receptor genes (EcRB1 and USP) and four downstream response genes (E93, Br-C, βFTZ-F1, and cathepsin L) at the pupal and pharate stages, respectively. Taken together, these genes serve as a resource for unraveling the mechanism underlying pupal-adult transition; these findings facilitate rearing of larvae more than once a year and biotechnological development through efficient termination of pupal diapause in A. pernyi in approximately half a month.